ANALISIS SISTEM PENJAMINAN MUTU PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH - Rasyida, Nuzla Aimmatu; Rosmasita, Hardhina; Tinus, Agus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education is a key in developing quality human resources, yet various problems persist, such as quality gaps, limited human resources, and suboptimal education management. This study aims to analyze the relationship between the Internal Quality Assurance System (SPMI), the External Quality Assurance System (SPME), accreditation, monitoring, and evaluation in improving educational quality. The study employed a qualitative descriptive approach through literature review. Data were obtained from various relevant scientific journals and analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that SPMI serves as a foundation for building a culture of quality through a continuous improvement cycle, while SPME, through accreditation, serves as external validation of the quality of educational institutions. Monitoring and evaluation are crucial instruments for controlling the implementation of standards and identifying gaps between planning and implementation. The discussion confirms that these components have a complementary relationship and form a continuous quality assurance cycle. The conclusion of this study is that the consistent integration of SPMI, SPME, accreditation, monitoring, and evaluation can improve the quality of learning, institutional governance, and graduate quality sustainably. Therefore, a quality assurance system needs to be implemented as an organizational culture in every educational institution.